Examination of The Effect of Trichloroacetic Acid Attachment and Instillation Methods on Ovarian Reserve and Dysplasic Changes in Ovarian Surface Epithelium - Sapmaz, Ekrem; Akpolat, Nusret (Fırat University, 2012)
Objective: To examine the effect of applying 3%, 50%, 75% and 95% concentrations of trichloroacetic acid by attachment and instillation methods for endometrial ablation on ovarian reserve and dysplasic changes in ovarian surface epithelium in rats. Material and Method: Ninety rats were included in a randomized, bloc-designed, concentration-matched study program. Group1: (n=10): Abdomen was opened and closed. The groups in which 3% (Group 2, n=10), 50% (Group 3, n=10), 75% (Group 4, n=10), and 95% (Group 5, n=10) TCA attachment was applied, after abdomen was opened and a 2 cm. lengthwise incision was made in the left uterine horn. The groups in which 0,1 ml of 3% (Group 6, n=10), 50% (Group 7, n=10), 75% (Group 8, n=10) and 95% (Group 9, n=10) TCA instillation was applied to the left uterine horn, after the abdomen was opened. Abdomens of all rats were opened 21 days later. Left oophorectomy was performed. Preparations were evaluated in terms of ovarian follicle reserve and changes in ovarian surface epithelium. Group 2 and Group 6, Group 3 and Group 7, Group 4 and Group 8, Group 5 and Group 9 were compared (MWU test). Kruskall Wallis variance analysis was employed in the comparison including all groups (p0.05). The comparison including all groups revealed that ovarian follicle reserve and surface epithelium changes were similar (p>0.05). Conclusion: Application of various concentrations of TCA by attachment and instillation methods for endometrial ablation doesn't have any unfavorable effect on ovarian reserve and ovarian surface epithelium in rats.

Amaç: %3, %50, %75 ve %95'lik konsantrasyonlardaki trikloroasetik asitin, endometriyal ablasyon için, atuşman ve instillasyon yöntemleri ile uygulanmasının rat over rezervi ile yüzey epitelindeki displazik değişiklikler üzerine etkisinin incelenmesi. Gereç ve Yöntem: 90 adet, Sprague Dawley rat, estrus fazında randomize blok düzenli (konsantrasyon karşılaştırmalı) çalışma programına alındı. Grup 1: (n=10): Batın açılıp kapatılan grup. Batın açılıp sol uterin horn distaline 2 cm'lik uzunlamasına insizyonu takiben, %3'lük TCA (Gruop 2, n=10), %50'lik TCA (Grup 3, n=10), %75'lik TCA (Grup 4, n=10) ve %95'lik TCA (Grup 5, n=10) atuşmanı yapılan grup. Batın açılıp sol uterin horna 0,1 ml %3'lük TCA (Grup 6, n=10), %50'lik TCA (Grup 7, n=10), %75'lik TCA (Grup 8, n=10) ve %95'lik TCA (Grup 9, n=10) instillasyonu yapılan grup. Tüm ratların 21 gün sonra estrus fazında batını açıldı. Sol ooferektomi yapıldı. Hematoksilen Eozin ile boyanan preparatlarda over folikül rezervi ve over yüzey epitel değişiklikleri değerlendirildi. Grup 2-Grup 6 ile, Grup 3-Grup 7 ile, Grup 4-Grup 8 ile, Grup 5-Grup 9 ile Mann Whitney U test ile karşılaştırıldı. Tüm grupların karşılaştırılması, Kruskall Wallis varyans analizi ile yapıldı. p0.05, Mann Whitney U test). Tüm grupların karşılaştırılmasında, over folikül rezervi ve yüzey epitel değişiklikleri benzer bulundu (p>0.05, Kruskall Wallis varyans analizi). Sonuç: Farklı konsantrasyonlardaki trikloroasetik asitin, endometriyal ablasyon için, atuşman ve instillasyon yöntemleri ile uygulanmasının rat over rezervi ve over yüzey epiteli üzerine olumsuz bir etkisi yoktur.
Trikloroasetik Asit Atuşman ve İnstillasyon Yöntemlerinin Over Rezervi ile Over Yüzey Epitelindeki Displazik Değişiklikler Üzerine Olan Etkisinin İncelenmesi